(untitled) (Research, Society and Development, 2021)
The educational system has tried to serve all students, from the smallest to the largest, ranging from small difficulties in teaching and learning, to their possible specific needs. In this context, Specialized Educational Assistance (AEE) is a space offered to students who have a Specific Educational Need (SEN), in a complementary way to regular education. This research aims to understand how the technologies of Augmented Reality (AR) and Virtual Reality (VR) can contribute in the teaching of Science to students with NEEs aged between 7 and 17 years old, from elementary school I and II, who carry out the ESA at the Roseana Sarney School Unit. The research carried out is of the quantitative-descriptive type. In addition to the aforementioned objective, we intend to quantitatively measure aspects such as attractiveness, perspicuity, efficiency, reliability, stimulation and novelty of the Digital Learning Objects (ODAS) used. AEE teachers, the school manager, the parents of students, and the students who perform this service participated in the experiment. As a result, it was possible to live a very promising experience with regard to teaching and learning in the ESA, it was observed that the students participating in the research showed a lot of interest in the use of the proposed technologies. Taking into account the objective of this research, it is clear the potential of AR and VR technologies in the teaching of Science to students with NEEs, these technologies were well accepted by students with SEN. As for science teaching, through AR and VR technologies it was possible for students to participate in the class in a more immersive way.